Entrepreneurship Marketing Development Model To Improve SMEs Economic Performance In Semarang - Cicik Harini; Novita Rahmayuna (Universitas Muhammadiyah Surakarta, 2023)
The empowerment of SMEs (micro small and enterprises) in the midst of globalization and high competition with ASEAN Economic Community (MEA) is expected to be an opportunity to exploit ASEAN regional policy in order to develop market as market player as its market. SMEs (micro small and enterprises) should be able to face various challenges, such as increasing product and service innovation, human resource and technology development, and expanding marketing. Marketing is a fundamental issue for small entrepreneurs. An important aspect of marketer is examined in the context of entrepreneurial efforts to see how marketing theory fits into the practice of entrepreneurship. But in the globalization era with the development of information technology is the essence, it is necessary development of entrepreneurship marketing that is able to reach all consumer in the world, that is through internet marketing or e-commerce. This research seeks to get a model of entrepreneurship marketing development in an effort to improve the performance of MSMEs (micro small and medium enterprises) in Semarang City. The hypothesis is tested using SEM analysis by estimating PLS parameters to assess the outer model and measurement model as well as assess the inner model. Based on the result, development of effective e-commerce has a positive influence on SMEs performance. But, entrepreneur marketing was rejected even though it has a positive influence on E-Commerce Development. This is because of the lack of understanding of the concepts, strategies, methods and market intelligence of the SMEs in Semarang.